2012
DOI: 10.1007/s10995-012-1211-8
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obese Women’s Perceptions About Making Healthy Change During Pregnancy: A Mixed Method Study

Abstract: Overweight and obesity during pregnancy is associated with risk of a range of adverse health outcomes. While intervention studies aim to promote behavioral change, little is known about the underlying psychological mechanisms facilitating and hindering change. The aim of this study was to evaluate overweight and obese women's perceptions of making behavior change during pregnancy. We explored beliefs through self-administrated questionnaires (n = 464) and semi-structured face-to-face interviews (n = 26). Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(139 citation statements)
references
References 26 publications
10
127
1
1
Order By: Relevance
“…However, studies conducted in this field have some limitations and focused on some aspects or behavioral changes during pregnancy in a retrospective approach. Nevertheless, pregnant women were highly motivated to adopt healthpromoting behaviors (32,34). Moreover, the motivating factor was the health of the fetus and achieving a desirable outcome in pregnancy (30,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies conducted in this field have some limitations and focused on some aspects or behavioral changes during pregnancy in a retrospective approach. Nevertheless, pregnant women were highly motivated to adopt healthpromoting behaviors (32,34). Moreover, the motivating factor was the health of the fetus and achieving a desirable outcome in pregnancy (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…Viau et al expressed that women experience worries related to the health of fetus, changes in daily activities, risks related to pregnancy such as abortion and social commitment during their pregnancy (31). Various studies on women implied fetal health was the most important motivating factor for making changes in the lifestyle (31,33,34). Addicted women's reasons to change their lifestyle were concerns about the health of the fetus and newborn, loving children and belief that they deserved to have the chance for a healthy life.…”
Section: Behavioral Changes In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Other qualitative studies examining perceptions of excessive weight gain have also reported that knowledge of neonatal risks is low (Groth et al, 2012; Herring et al, 2012; Sui et al, 2013). Infants born to mothers with excessive weight gain are at increased risk for many health complications, including low 5-minute Apgar scores, hypoglycemia, large for gestational age, and future overweight or obesity as compared with women who gain within the recommended guidelines (Olson et al, 2009; Stotland et al, 2006; Vesco et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified misperceptions about the risks and benefits of exercise during pregnancy (Evenson & Bradley, 2010; Goodrich et al, 2013; Padmanabhan et al, 2015). While it appears the health benefits of proper nutrition are better understood, women consistently cite many barriers to healthy eating, including lack of self-control in response to cravings (Goodrich et al, 2013; Padmanabhan et al, 2015; Sui et al, 2013). Some data also suggest there may be racial or ethnic differences in how women view these topics, particularly for weight gain and exercise (Brooten et al, 2012; Evenson & Bradley, 2010; Groth & Kearney, 2009; Groth et al, 2012; Sui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%